Blue light hazard measurement and uncertainty analysis of smartphones - Zhang, Y.; Saukova, Y. N. (БНТУ, 2023)
Based on the conclusion obtained from the questionnaire survey: Smartphones are currently the electronic device that has been used the longest and most frequently. The blue light harm that smart phones may cause to the retina was measured. Uncertainty analysis of photobiosafety measurements of smartphones and measurement recommendations are given.
Измерение опасности синего света и анализ неопределенности смартфонов